Inclusion of Persons with Disabilities (Pwds) into the Mainstream Labor Force in the Province of Camarines Norte - Asay, Malyn Manalo; Asay, Angeles M. (MultiTech Publisher, 2024)
A study in Camarines Norte focused on integrating persons with disabilities (PWDs) into the labor force. It aimed to understand their demographics, required skills, and inclusion challenges. This study used descriptive methods in interviews and questionnaires and quota sampling in selecting the respondents totaling 375 respondents, the study found that most PWDs were male, single, with orthopedic disabilities, and high school graduates. They were predominantly non-permanent and self-employed. Recommendations include dedicated job fairs, start-up funds, and reserved employment quotas in both public and private sectors. The results concludes that the Provincial Government and relevant agencies are urged to enhance job opportunities, provide skills training, and enforce existing employment quotas for PWDs. Overall, PWDs are seen as committed assets to companies